Single scan SeHCAT studies: a model for the prediction of the 3-h counts. Issue 11 (November 2021) - Smout, Alexander; Scuffham, James; Hinton, Paul
Abstract : Objectives: As part of the 75-Selenium homocholic acid taurine (SeHCAT) study, counts are acquired as a baseline to allow the calculation of the retention at 7 days. In this work, we evaluated whether it was possible to replace the baseline image with a predictive model based on the patient's height and weight. Method: Height and weight data from 723 patients scanned at three hospitals using seven gamma cameras were compiled. A number of different models were trialled, with fitting parameters determined by regression. A predictive model based on height and logarithm of weight was found to have the best correlation with the measured counts in the 3-h study. Results: There was a strong correlation ( R 2 = 0.91) between the measured counts and the predicted counts using a model based on height and logarithm of weight. Treating the standard SeHCAT test result as the gold standard, the test result when predicted baseline counts were used had a sensitivity and specificity of 97.5 and 98.0%, respectively, at a threshold of 15%. In total 694/723 (96.0%) of patients had no change to their severity grading when using the predicted baseline counts. Conclusion: This work presents a model that was able to predict the counts in the 3 h SeHCAT study for patients on seven gamma cameras. This can enable a single scan study, giving significant savings to patient and staff time and imaging resources.